PROSPEK PENGEMBANGAN USAHATANI BAWANG MERAH DALAM UPAYA PENINGKATAN PENDAPATAN MASYARAKAT DI DESA ILOMANGGA KECAMATAN TABONGO - Abdussamad, Siti Nurcahyati; Imran, Supriyo; Indriani, Ria (Universitas Negeri Gorontalo, 2024)
The purpose of this study was to analyze the income and feasibility of shallot farming in Ilomangga Village, Tabongo Subdistrict and to analyze the feasibility of shallot farming in Ilomangga Village, Tabongo Subdistrict. This research was conducted from November to January 2024 with a sample of 20 respondents. The research method used is the survey method. Data analysis used in this research is Income analysis, Return Cost ratio (R/C) method. The results of this study indicate that Ilomangga Village has the potential to develop business opportunities for Red Onion commodities in an effort to increase community income. This can be seen from the accessibility of the Ilomangga Village shallot shallot farming business which is quite good, with an average income of Rp 17,151,296.2. Onion farming in Ilomangga Village, Tabongo Subdistrict is feasible because the R / C Ratio value of 2.19 indicates that every Rp.1 cost expenditure will receive Rp.2.19, meaning that the Onion farming business in Ilomangga Village, Tabongo Subdistrict is feasible.